2007
DOI: 10.1007/s11095-007-9382-5
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Biosynthetic Nanobiomaterials (IBNs) for Hyperthermic Gene Delivery

Abstract: K8-ELP(1-60) was successfully designed and purified through recombinant means with efficient and stable condensation of pDNA at N/P ratios>0.25 and polyplex particle size<115 nm. MCF-7 cells successfully expressed EGFP with minimal cytotoxicity compared to positive controls; moreover, polyplexes retained sharp, thermotransitive kinetics within a narrow Tt range at clinically relevant hyperthermic temperatures, where the decrease of Tt was due to the increased hydrophobicity upon charge neutralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 43 publications
(47 reference statements)
3
70
0
Order By: Relevance
“…Although positively charged ELPs have been created by inclusion of cationic guest residues [63, 64], this low charge density was not ideal for DNA condensation as compared to the high charge density provided by contiguous cationic residues. ELPs for DNA condensation have thus been specifically designed as a genetic fusion of an ELP and a cationic domain consisting of an eight-residue oligolysine peptide [54]. This cationic ELP successfully condensed plasmid DNA into particles approximately 32–115 nm in radius, depending on the N/P ratio (the ratio of cationic amine groups contributed by the ELP to anionic phosphate groups contributed by the DNA).…”
Section: Architectures and Assemblies Of Elp Drug Carriersmentioning
confidence: 99%
“…Although positively charged ELPs have been created by inclusion of cationic guest residues [63, 64], this low charge density was not ideal for DNA condensation as compared to the high charge density provided by contiguous cationic residues. ELPs for DNA condensation have thus been specifically designed as a genetic fusion of an ELP and a cationic domain consisting of an eight-residue oligolysine peptide [54]. This cationic ELP successfully condensed plasmid DNA into particles approximately 32–115 nm in radius, depending on the N/P ratio (the ratio of cationic amine groups contributed by the ELP to anionic phosphate groups contributed by the DNA).…”
Section: Architectures and Assemblies Of Elp Drug Carriersmentioning
confidence: 99%
“…Bi-functional RCPs were also synthesized on a cationic oligomer block fused to an ELP, but in the absence of an endosmal escape mechanism the system lead to poor efficiency. [131] Tri-functional biopolymers were then synthesized in an attempt to achieve efficient gene transfer from RCPs. These polymers consisted of lysine-histidine (K-H) residues with a fibroblast growth factor 2 (FGF2) fusion.…”
Section: Recombinant Cationic Polymersmentioning
confidence: 99%
“…Thus, polymers are considered the most receptive for facile modification with various substituents or by block copolymerization. For example, it has been revealed that the feasibility of nanoparticles vectors that optimal polymer compositions such as molecular weight and pKa can be selected plays a pivotal role in facilitating the release and endosomal escape of pDNA and eventually induces high transfection efficiency [36]. In addition, various shapes of nanoparticles can be achieved by varying the polylysine (PLL) counterion present at the time of compaction [37].…”
Section: Variable Physicochemical Properties For Gene Loadingmentioning
confidence: 99%